Experimental and Numerical Study of Fatigue Damage Assessment under Combined High and Low Cycle Loading - Chaoshuai Han; Xianqiang Qu; Yongliang Ma; Dexin Shi (Shock and Vibration)
This paper studies fatigue damage under combined high and low cycle loading. The interaction of two types of loading will greatly reduce fatigue life of structures. Existing methods usually neglect the minor high cycle loading, which obviously underestimates the total fatigue damage. To solve this problem, four methods are proposed and extended for the case of combined loading. Numerical simulations based on the superposition of two sine waves are performed. Experiments are carried out using “DH36” smooth round-type specimens. Damage predictions results by four methods are compared to the experimental results. It is concluded that some methods give satisfactory fatigue damage estimations and can be regarded as a safe design tool in engineering application.